Sensibilidade de fungos deteriorantes e toxigênicos à águas eletrolisadas e sanitizantes químicos - Lemos, Jéssica Gonçalves (2021)
Fungi are the main microorganisms that spoilage cheese and bread, causing great economic damage to industries. It is known that contaminated raw material and ambient air are the main causes of the loss of these food products. In addition to these spoilaging fungi, there are toxigenic fungi, also found in the dairy and bakery industries, which produce, for example, aflatoxins and ochratoxin A, which is another concern for the industry, mainly because these mycotoxins can cause kidney, liver, and neuronal changes in animals and humans. One of the ways to reduce fungal contamination of the environment and thereby to prevent contamination of foodstuffs in stages of processing and industrial post-processing is the use of substances with antifungal activity. For this purpose, the effectiveness of five chemical sanitizers in different concentrations peracetic acid (0.3%, 0.6%, 1%), biguanide (2%, 3.5%, 5%), benzalkonium chloride (0.3 %, 1.2%, 2%), sodium hypochlorite (0.5%, 0.75%, 1%), and iodine (0.2%, 0.6%, 1%) against toxigenic strains of Aspergillus flavus, Aspergillus parasiticus, Aspergillus nomius Aspergillus niger, Aspergillus carbonarius, Aspergillus ochraceus, and Aspergillus westerdijkiae. Electrolyzed waters, a new non-polluting and environmentally friendly technology, were also evaluated, at chlorine concentrations of 60, 85 and 121 ppm and their corresponding basic electrolyzed waters for toxigenic species inactivation; and the concentration of 85 ppm, against deteriorating fungi of bread Penicillium roqueforti and Hyphopichia burtonii and deteriorating fungi of cheese P. roqueforti and Penicillium commune. The tests followed the protocol proposed by the European Committee for Standardization that classifies a sanitizer as effective if it reduces the initial microorganism population by 3 log (99.99%). After the tests with the toxigenic fungi, it was observed that benzalkonium chloride and iodine are the most recommended sanitizers for eliminating the fungi Aspergillus section Flavi and Nigri. For the control of Aspergillis section Circumdati the best agent is peracetic acid. Biguanide, sodium hypochlorite, and electrolyzed waters at the concentrations used were not effective. Regarding spoilaging fungi, it was found that the electrolyzed water obtained better efficacy against the standard fungi Candida albicans and Aspergillus brasiliensis and achieved medium efficacy of 90% for the problem fungi for the industry. Still on the theme of contamination by toxigenic fungi in the cheese, bread and meat products industries, we sought to revise the last 20 years of scientific literature, looking for articles that relate cases of air contamination with contamination of the final product with toxigenic fungi. It was found that the genus Aspergillus was more related to contamination of bakery products, and the genus Penicilium to contamination of meat and dairy products. With these studies, it can be observed that the choice of the best sanitizing agent depends on each strain and species of fungi, as well as the concentration and compounds to be used. And that the literature still has a gap with respect to data that correlate contamination of the environment with toxigenic fungi and the final product.